The Potential of Shortening the Adaptation of Nellore Cattle to High-Concentrate Diets Using Only Virginiamycin as Sole Feed Additive - Rigueiro, André L. N.; Squizatti, Mariana M.; Silvestre, Antonio M.; Pinto, Ana C. J.; Estevam, Daniela D.; Felizari, Luana D.; Dias, Evandro F. F.; Demartini, Breno L.; Nunes, Ana B. P. C.; Costa, Victor C. M.; Caixeta, Eduardo L.; Santi, Pedro F.; et al. (Frontiers in Veterinary Science, 2021)
Feedlot cattle are usually adapted to high-concentrate diets containing sodium monensin (MON) in more than 14 d. However, for finishing diets containing lower energy content, the use of MON during adaptation may hold dry matter intake (DMI), and virginiamycin (VM) may be an alternative. This study was designed to determine the potential of shortening the adaptation of Nellore cattle to high-concentrate diets using only VM as sole feed additive on feedlot performance, feeding behavior, and ruminal and cecum morphometrics. The experiment was designed as a completely randomized block, replicated 6 times (4 animals/pen) in which 120 Nellore bulls (390.4±19.0 kg) were fed in 30 pens for 111 d according to the treatments: 1) MON and adaptation for 14 d (MON14); 2) MON+VM and adaptation for 14 d (MONVM14); 3) VM and adaptation for 14 d (VM14); 4) VM and adaptation for 9 d (VM9); and 5) VM and adaptation for 6 d (VM6). At the end of the adaptation, 30 animals (n=1 per pen) were randomly slaughtered for rumen and cecum evaluations. The remaining 90 bulls were harvested at the end of the study. No effects of treatments were observed (P<0.10) for final body weight, average daily gain and hot carcass weight. Cattle fed VM14 presented greater (P≤0.03) DMI, expressed as % of body weight, than animals fed either MON14 or MONVM14; however, cattle fed either MON14 or MONVM14 improved (P≤0.02) gain-to-feed ratio by 10.4% or 8.1%, respectively, when compared to bulls fed VM14. Bulls fed VM14 had smaller (P<0.05) papillae area (0.34 vs. 0.42 cm2), and rumen absorptive surface area (28.9 vs. 33.8 cm2) than those fed MON14. The shortening of the adaptation period linearly decreased the 12th rib fat (P=0.02) and Biceps femoris fat daily gain (P=0.02) of Nellore bulls fed only VM, which linearly decreased final Biceps femoris fat thickness (P<0.01). Feedlot cattle fed VM as sole feed additive should not be adapted to high-concentrate diets in less than 14 d. Regardless of either adaptation length or feed additive, feedlot cattle need at least 14 d to adapt to finishing diets.